2022
DOI: 10.3389/fgene.2022.947120
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Reveals the Expression Profiles of circRNAs and Indicates Hsa_circ_0070562 as a Pro-osteogenic Factor in Bone Marrow-Derived Mesenchymal Stem Cells of Patients With Ankylosing Spondylitis

Abstract: Recent studies have reported that circular RNAs (circRNAs) play a crucial regulatory role in a variety of human diseases. However, the roles of circRNAs in pathological osteogenesis in ankylosing spondylitis (AS) remain unclear. We conducted circRNA and miRNA expression profiling of osteogenically differentiated bone marrow-derived mesenchymal stem cells (BMSCs) of patients with AS compared with those of healthy donors (HDs) by RNA sequencing (RNA-seq). Results showed that a total of 31806 circRNAs were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Tang YP found that hsa_circRNA_012732 has the potential to be an indicator of disease activity, while hsa_circRNA_001544 could serve as a molecular marker for AS diagnosis [8]. Furthermore, Wang S identi ed hsa_circ_0070562 as a proosteogenic factor in AS [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tang YP found that hsa_circRNA_012732 has the potential to be an indicator of disease activity, while hsa_circRNA_001544 could serve as a molecular marker for AS diagnosis [8]. Furthermore, Wang S identi ed hsa_circ_0070562 as a proosteogenic factor in AS [9].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ceRNA regulation has been found to play an important role in ankylosing spondylitis (AS), which is a subtype of JSpA [4]. Several studies have investigated the regulatory role of circRNAs in AS, highlighting the potential of these molecules as therapeutic targets for the disease [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation